LEGAL AND NON-LEGAL AGRICULTURAL PRACTICES: TOWARD A SUSTAINABLE FUTURE IN MALAYSIA’S PALM OIL INDUSTRY - Kamaruddin, Hanim; Wahab, Harlida Abdul; Anuar, Haslinda Mohd (Indonesia Law Review, 2018)
As a major global producer of palm oil products, Malaysia is familiar with criticisms of its palm oil cultivation, poor agricultural practices and decisions during the planting process. Loss of biodiversity and deforestation resulting from unsustainable palm oil practices are perceived as major setbacks for the environment in Malaysia. However, at the same time as Malaysia stands committed to the palm oil industry and its contribution to job growth and poverty reduction, the relevant stakeholders are creating strategies for sustainable production. Together with relevant environmental laws to prevent and control impacts from climate change, loss of biodiversity and deforestation, environmental impact assessment (EIA) procedures to limit environmental impacts are also being applied. Many legal and non-legal measures to ensure sustainable palm oil production practices have been continuously debated, created or implemented over the past decades. These include certification schemes, penalties for environmental offenses, imposing environmental taxes or incentives as corrective and rehabilitative tools, and contributions to an Environmental Fund, as provided in the Environmental Quality Act (EQA) 1974. Furthermore, any new initiatives must ensure that palm oil cultivation practices adhere to and embrace the principles envisaged in the UN Sustainable Development Goals (SDGs) 2030, Roundtable Sustainable Palm Oil (RSPO), and Malaysia Sustainable Palm Oil (MSPO), in order to achieve SDGs 2030.